The Life in the Scroll: Medieval Notaries as Mediators in the Trial, in Wills and in Contracts: Peer-reviewed article (Italian Review of Legal History, 2022)
The essay brings together the results of two researches carried out within the project: Limen, Languages of Notarial Mediation between the Middle Ages and the Modern Age, presented in July 2019 at the Extraordinary Call for Interdepartmental Projects of the University of Milan and considered worthy of funding with the recognition of the Seal of excellence in 2020. In the two interventions previously published in italian language (L’attività di mediazione del notaio nella Summa di Rolandino in Mediazione Notarile. Forme e linguaggi tra Medioevo ed Età Moderna, a cura di Alessandra Bassani, Marta Mangini e Fabrizio Pagnoni, Quaderni degli Studi di Storia Medievale e di Diplomatica VI, Milano Pearson 2022 e Notaio mediatore: la distanza fra la vita e la pergamena in Giustizia, istituzioni e notai tra i secoli XII e XVII in una prospettiva europea. In ricordo di Dino Puncuh, a cura di Denise Bezzina - Marta Calleri - Marta Luigina Mangini - Valentina Ruzzin, Notariorum Itinera Varia 6, Società Ligure di Storia Patria, Genova 2022) the Author used the hermeneutic tool of the ‘function’ of mediation to connect the results of the historical-legal research with those equally in-depth of the historians of society, institutions and the economy. Thus the medieval notary’s activity emerges from the examination of testimonial depositions, mortis causa deeds and contracts of writing and discipleship: the notary was protagonist of the institutional, social and economic life of the medieval municipality and also a spiritual and family mediator in his customers’ most intimate and personal life.
Keywords: Notary; middle ages; trial witnesses; mortis causa deeds; contracts